The Application of Non-orthogonal Laguerre L2 Basis to the Calculation of the Differential and Integrated Cross Sections for the Electron Impact Elastic and Excitation of the 21S, 21P, 23S, 23P States of Helium at Intermediate Energy - Agus Kartono; Toto Winata (Jurnal Matematika & Sains, 2007)
The non-orthogonal Laguerre L2 basis has been applied in the intermediate energy region (30, 40 and 50 eV) for the electron impact elastic and excitation of 21S, 21P, 23S and 23P states of helium. Differential and integrated cross sections are calculated and compared with recent experiments. The results for each case are discussed and compared with other calculation. It is found that the results agree quite well with experiments and with the other results.